Engineered neural tissue made using hydrogels derived from decellularised tissues for the regeneration of peripheral nerves. (February 2023) - Kellaway, Simon C.; Roberton, Victoria; Jones, Joshua N.; Loczenski, Rabea; Phillips, James B.; White, Lisa J.
Abstract: Engineered neural tissue (EngNT) promotes in vivo axonal regeneration. Decellularised materials (dECM) are complex biologic scaffolds that can improve the cellular environment and also encourage positive tissue remodelling in vivo . We hypothesised that we could incorporate a hydrogel derived from a decellularised tissue (dECMh) into EngNT, thereby providing an alternative to the currently used purified collagen I hydrogel for the first time. Decellularisation was carried out on bone (B-ECM), liver (LIV-ECM), and small intestinal (SIS-ECM) tissues and the resultant dECM was biochemically and mechanically characterised. dECMh differed in mechanical and biochemical properties that likely had an effect on Schwann cell behaviour observed in metabolic activity and contraction profiles. Cellular alignment was observed in tethered moulds within the B-ECM and SIS-ECM derived hydrogels only. No difference was observed in dorsal root ganglia (DRG) neurite extension between the dECMh groups and collagen I groups when applied as a coverslip coating, however, when DRG were seeded atop EngNT constructs, only the B-ECM derived EngNT performed similarly to collagen I derived EngNT. B-ECM EngNT further exhibited similar axonal regeneration to collagen I EngNT in a 10 mm gap rat sciatic nerve injury model after 4 weeks. Our results have shown that various dECMh can be utilised to produce EngNT that can promote neurite extension in vitro and axonal regeneration in vivo . Statement of significance: Nerve autografts are undesirable due to the sacrifice of a patient's own nerve tissue to repair injuries. Engineered neural tissue (EngNT) is a type of living artificial tissue that has been developed to overcome this. To date, only a collagen hydrogel has been shown to be effective in the production and utilisation of EngNT in animal models. Hydrogels may be made from decellularised extracellular matrix derived from many tissues. In this study we showed that hydrogels from various tissues may be used to create EngNT and one was shown to comparable to the currently used collagen based EngNT in a rat sciatic nerve injry model. Graphical abstract: Image, graphical abstract